2009 IEEE International Conference on Communications 2009
DOI: 10.1109/icc.2009.5198842
|View full text |Cite
|
Sign up to set email alerts
|

Compressed Sensing Maximum Likelihood Channel Estimation for Ultra-Wideband Impulse Radio

Abstract: Abstract-One of the most attractive features of ultrawideband impulse radio is the collection of rich multipath with the transmission of ultra-short pulses. Exploiting the rich multipath diversity with channel estimating Rake receivers enables significant energy capture, higher performance and flexibility than suboptimal receivers. Although data-aided (DA) maximum likelihood (ML) channel estimator shows a promising performance, its implementation is restricted by the Nyquist sampling criterion. The emerging th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…For the CS-based transceiver design, the main goal is to detect the UWB signal with reduced sampling rate and yet with negligible performance degradation [15][16][17]. For the CS-based channel estimation, the main goal is to estimate the sparse channel with reduced number of observations [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…For the CS-based transceiver design, the main goal is to detect the UWB signal with reduced sampling rate and yet with negligible performance degradation [15][16][17]. For the CS-based channel estimation, the main goal is to estimate the sparse channel with reduced number of observations [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…This work solely focuses on channel estimation for one pulse position modulation (PPM) time-hopping (TH) UWB transceiver and does not take into account the effects of multi-user interference (MUI) and other external sources of interference. The work in [9] proposes a compressed sensing maximum likelihood (CSML) channel estimator in order to reduce the Nyquist sampling rate, which renders the implementation of UWB systems easier. The authors have shown that while retaining the noise statistics formulation of ML to achieve a reliable performance, the sampling rate is reduced significantly.…”
Section: Introductionmentioning
confidence: 99%
“…As the IR-UWB signals have resolvable multipath with a sparse structure at the receiver, the application of CS theory to UWB channel estimation has also found wide interest in the UWB community. For the CS based UWB channel estimation, the main goal has been to estimate the sparse channel with reduced number of observations (Paredes et al, 2007;Liu & Lu, 2009;Naini et al, 2009).That is equivalent to reducing the sampling rate at the receiver. In (Paredes et al, 2007), a channel detection method based on the Matching Pursuit algorithm is proposed, where the path delays and gains are calculated iteratively.…”
Section: Introductionmentioning
confidence: 99%
“…In (Paredes et al, 2007), a channel detection method based on the Matching Pursuit algorithm is proposed, where the path delays and gains are calculated iteratively. In (Liu & Lu, 2009), the authors combine the maximum likelihood (ML) approach with the CS theory. In (Naini et al, 2009), a spread spectrum modulation structure is placed before the measurement matrix to enhance the estimation performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation